Superposición del síndrome de intestino irritable y dispepsia funcional basados en criterios ROMA III en estudiantes de medicina de una universidad privada de Lima, Perú - Vargas Matos, Iván (2015)
Aims: To determine the prevalence of irritable bowel syndrome and functional dyspepsia in medical students from a private university in Lima, Peru. Furthermore, to determine the associated factors with these diseases. Material and methods: Observational descriptive and retrospective cross sectional study. Medical students from a private university in Lima were surveyed using a Rome III questionnaire for functional disorders and the STEPwise auto survey for defining the variables of alcohol and tobacco. For data analysis the Stata 11.0 program was used. Results: Of the 608 students, 543 answered the questionnaire. The prevalence of Irritable Bowel Syndrome was 12.4%, 16.9% of dyspepsia, and of both diseases simultaneously, a prevalence of 7.1% was found. Alcohol consumption in the total population was 89.4% and 29.0% of tobacco. Association between both disorders was found (OR 10.47, 95% CI 5.08 to 21.55; p <0.001), dyspepsia was associated with sex (OR: 0.16, 95% CI 0.07 to 0.36 p <0.001), with alcohol consumption (OR: 5.22, 95% CI 23.99 1,13- p = 0.034) and with irritable bowel syndrome (OR: 9.88, 95% CI 4.78 to 20.46 p <0.001). Both conditions together were associated with sex (OR: 0.20, 95% CI from 0.06 to 0.60 p = 0.004) and daily consumption of tobacco (OR: 3.23, 95% CI 1.17 to 8.89 p = 0.023). Conclusion: A prevalence of 12.4% of Irritable Bowel Syndrome and 16.9% of dyspepsia was determined. An overlap of 7.1% of these diseases was reported.